Pengaruh Transfer Pricing, Inventory Intensity, Capital Intensity Terhadap Penghindaran Pajak - Ramadhan, Daniel; Budiwitjaksono, Gideon Setyo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the impact of transfer pricing, inventory intensity, and capital intensity on tax avoidance in coal mining sub-sector companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. Tax avoidance is a critical issue due to its effect on optimizing state revenue. The study employs a quantitative approach with purposive sampling, resulting in a sample of 12 companies analyzed over five years, yielding 60 observational data points. Secondary data were obtained from published annual reports and financial statements. Data analysis was conducted using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the assistance of SmartPLS 3.0 software. The results indicate that transfer pricing and capital intensity have no significant impact on tax avoidance. Meanwhile, inventory intensity has a positive and significant effect on tax avoidance, suggesting that inventory manipulation may be used to reduce tax burdens. These findings contribute to regulators in tightening oversight on inventory management in tax policies and to companies in formulating ethical and regulation-compliant tax strategies.